Dental health among adolescents in Kosovo, investigating risk factors and prevalence trends - Hoxha, Suela; Veseli, Jaser; Hoxha, Xheneta; Hoxha, Fatime (Intelektual Pustaka Media Utama, 2025)
Dental caries remains a critical public health issue among children in Kosovo, caused by a complex interplay of dietary habits that contribute to the deterioration of oral health. This study aimed to evaluate the prevalence of dental caries in adolescents aged 12 to 16 years and to identify associated risk factors. A cross-sectional study design was employed, involving 120 students from elementary schools in the Suhareka municipality, who underwent clinical oral examinations and completed self-administered questionnaires between January and June 2023. The caries prevalence was quantified using the decayed, missing, and filled teeth (DMFT) index. Statistical analysis, performed using SPSS 26.0, demonstrated a significant association between dietary behaviors and caries incidence, with higher consumption rates correlating with increased DMFT scores. ANOVA and Fisher’s post hoc tests were utilized to assess variables impacting caries progression, while the Chi-square test of independence was applied for intergroup comparisons. The status of permanent dentition was systematically evaluated through the DMFT index, with results interpreted within a 95% confidence interval. Both intrinsic and extrinsic factors affecting enamel resilience were explored, with an emphasis on developing targeted strategies to prevent dental deterioration and enhance oral health among adolescents. The outcomes of this study offer valuable insights for improving pediatric oral health in Kosovo and provide evidence-based recommendations for policymakers and healthcare professionals to formulate effective preventive strategies and public health interventions in similar demographic contexts.